Bridging the Holistic–Skills Gap in Islamic Vocational Education: Management Practices and Graduate Employability - Sukardi, Sukardi; Usman, Fadly (Reforma: Jurnal Pendidikan dan Pembelajaran, 2025)
This study critically examines the role of Islamic education management in reducing the misalignment between graduate competencies and workforce demands in an Islamic vocational context. Conducted at Nahdlatul Ulama 1 Karanggeneng Vocational High School, Indonesia, the research investigates how managerial decisions shape graduate readiness amid the dual mission of character formation and skills preparation. Using a qualitative case study design, data were collected through in-depth interviews with six informants (school leaders, teachers, and alumni), participant observation, and analysis of national tracer study data. The findings demonstrate a dualistic pattern: management is highly effective in strengthening students’ spiritual discipline and character through structured religious and organizational programs, yet remains deficient in establishing industry partnerships and embedding digital competencies. This imbalance produces uneven employability outcomes across majors, most notably reflected in the 75.5% absorption rate in Computer Networking compared to substantially lower outcomes in other fields. These disparities indicate a persistent “holistic–utilitarian disconnect” between internal value-based practices and external labor market expectations. The study concludes that a strategic shift is necessary, emphasizing three priorities: professionalizing industry linkages across all majors, systematically integrating digital fluency within the curriculum, and implementing targeted interventions to enhance student confidence and career navigation skills. These actionable recommendations provide a management-oriented framework for Islamic vocational institutions to better harmonize spiritual formation with labor market relevance and strengthen their graduates’ competitiveness in an evolving workforce landscape.